Factors Associated with Abortion Complications after the Implementation of a Surveillance Network (MUSA Network) in a University Hospital - Camila Ayume Amano Cavalari; Nelio Neves Veiga-Junior; Beatriz Deguti Kajiura; Caroline Eugeni; Barbara Virgínia Gonçalves Tavares; Luiz Francisco Baccaro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To evaluate the factors associated with abortion complications following the implementation of the good-practice surveillance network Mujeres en Situación de Aborto (Women Undergoing Abortion, MUSA, in Spanish). Methods A cross-sectional study withwomen who underwent abortion due to any cause and in any age group at UNICAMP Women's Hospital (part of MUSA network), Campinas, Brazil, between July 2017 and Agust 2019. The dependent variable was the presence of any abortion-related complications during hospitalization. The independent variables were clinical and sociodemographic data. The Chi-square test, the Mann-Whitney test, and multiple logistic regression were used for the statistical analysis. Results Overall, 305 women were enrolled (mean±standard deviation [SD] for age: 29.79±7.54 years). The mean gestational age was 11.17 (±3.63) weeks. Accidental pregnancy occurred in 196 (64.5%) cases, 91 (29.8%) due to contraception failure. At least 1 complication was observed in 23 (7.54%) women, and 8 (34.8%) of them had more than 1. The most frequent complications were excessive bleeding and infection. The factors independently associated with a higher prevalence of complications were higher gestational ages (odds ratio [OR]: 1.22; 95% confidence interval [95%CI]: 1.09 to 1.37) and contraceptive failure (OR: 3.4; 95%CI: 1.32 to 8.71). Conclusion Higher gestational age and contraceptive failure were associated with a higher prevalence of complications. This information obtained through the surveillance network can be used to improve care, particularly in women more susceptible to unfavorable outcomes.